Casing deformation relieving cement paste system as well as preparation method and application thereof

By using a cement slurry system containing glass beads and fiber carbon materials in shale gas wells, the problem of anti-shelving problems in cementing under complex sheathing conditions is solved, and the efficient compression resistance and elastic modulus of cement stone is achieved. Reduced, providing deformation buffer space, improving wellbore sealing and shale gas development efficiency.

CN119219367AActive Publication Date: 2024-12-31CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202310795333.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The existing technology is not universal under complex sheathing conditions, and it is difficult to effectively alleviate the problem of anti-shelving change in shale gas well cementing, affecting the wellbore sealing and efficient development of shale gas.

Method used

A system for relieving cement slurry is adopted, which includes G-grade oil well cement, microsilicon, glass microbeads, reinforcement materials, toughening materials, stabilizers, dispersants, water-reducing agents, retarders, and defoaming agents. And foam inhibitors, by adding glass beads with low compressive strength and toughening materials made of fiber and carbon materials, the elastic modulus of cement stone is reduced and deformation buffer space is provided.

Benefits of technology

Without affecting the compressive strength of cement stone, the ability of cement stone to relieve sheath transformation is improved. The compressive strength of cement stone formed in 7 days is greater than 20MPa and the elastic modulus is less than 5GPa, which meets the cementing construction requirements and slides in the formation. Active crushing during movement provides deformation space to prevent casing from deforming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004314844640000071
    Figure BDA0004314844640000071
Patent Text Reader

Abstract

The invention provides a casing deformation relieving cement paste system as well as a preparation method and application thereof. The casing deformation relieving cement paste system comprises the following raw materials in percentage by weight: 100 parts of G-grade oil well cement, 3-6 parts of micro-silicon, 15-50 parts of glass beads, 3-6 parts of a reinforcing material and 3-5 parts of a toughening material, wherein the toughening material is formed by compounding fibers and a carbon material in a mass ratio of (2-4): 1, the fibers comprise one or a combination of more than two of basalt fibers, alumina fibers and silicon carbide fibers, and the carbon material comprises carbon nanotubes and / or expanded graphite; the compressive strength of the glass beads ranges from 3000 psi to 5000 psi. The casing deformation relieving cement paste system meets the well cementation construction requirement, meanwhile, when the elastic modulus of set cement is low and the stratum slippage amount is large, active breaking can be conducted to replace space, space is provided for casing deformation, and the casing deformation preventing and relieving effects are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shale gas cementing, and in particular to a casing change mitigation cement slurry system and a preparation method and application thereof. Background Art

[0002] At present, the common methods used to prevent casing deformation in shale gas well cementing are to increase the thickness of cement sheath or casing wall, reduce the elastic modulus of cement stone, etc. to alleviate the casing deformation phenomenon. There is no cement slurry system specifically used for preventing casing deformation in shale gas well cementing.

[0003] CN202210052442.5 discloses a high-density anti-channeling tough cement slurry system for shale gas cementing, and its preparation method and application, which includes G-grade cement, water, composite weighting agent, nano anti-channeling agent, toughening agent, fluid loss reducer, retarder, dispersant and defoaming agent. Among them, the addition of nano anti-channeling agent not only has no negative impact on the construction performance of cement slurry, but also can promote the formation of early strength of cement, reduce the permeability of cement stone, make the structure of cement stone more uniform and dense, and effectively enhance the anti-channeling property of cement stone.

[0004] CN201910113067.9 discloses a cementing slurry system suitable for large-scale staged fracturing of shale gas horizontal wells, which mainly includes 100 parts of oil well cement, 43-46 parts of fresh water, 2-4 parts of elastic and toughening agent, 1-2 parts of anti-channeling agent, 1-3 parts of fluid loss reducer, 0.4-0.6 parts of dispersant, 1-1.5 parts of swelling agent, 0.5-2.0 parts of retarder, and 0.1-0.5 parts of defoaming agent. The elastic and toughening agent is a rubber fiber with a specific surface area ≥7m / g and a volume compression rate ≥5%, or a mixture of the rubber fiber and rubber particles. The cementing slurry system of this technology has excellent comprehensive properties such as thickening and anti-channeling performance, elasticity and toughness, which can effectively realize the synchronous deformation of the cement ring and casing when the cement ring is subjected to the alternating load of staged fracturing, ensuring the long-term integrity of the wellbore seal of the shale gas horizontal well during the later reservoir transformation and gas trial production operations, effectively preventing the occurrence of casing annulus pressure, and providing effective guarantee for the long-term production and large-scale fracturing of shale gas horizontal wells.

[0005] CN201410471036.8 discloses a toughening and anti-channeling agent for cement and toughening cement for shale gas horizontal well cementing. The technology relates to a cement slurry used in shale gas horizontal well cementing and a toughening additive added therein. The toughening and anti-channeling agent for cement is prepared by mixing styrene-butadiene rubber powder and redispersible latex powder in a mass ratio of 2:1, wherein the styrene-butadiene rubber powder is treated as follows before use: firstly prepare a silane coupling agent solution with a mass percentage of 1.5%, add styrene-butadiene rubber powder thereto, filter after standing for 24 hours, and dry it to make cement slurry. The system performance is stable, the thickening time is easy to adjust, the water loss is less than 30ml, the free liquid at a 45-degree inclination angle and the upper and lower density differences are both 0.50℃, the compressive strength is greater than 30Mpa for 24h, the applicable temperature range is 50-120℃, and the thickening time is 110-240min. The toughening and anti-channeling agent for cement is added to the toughening cement for shale gas horizontal well cementing. The cement slurry system produced therefrom has good stability and low water loss and separation, and can meet the requirements of shale gas horizontal well multi-stage fracturing for cement slurry systems.

[0006] The above existing technologies have achieved results in preventing casing change, but they are still not universally applicable under complex casing change conditions. Therefore, it is urgent to carry out research on shale gas cementing slurry to alleviate casing change, improve the cementing quality of shale gas wells, ensure the safety of casing service, and ensure the efficient development of shale gas. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a sleeve change relief cement slurry system and a preparation method thereof. The cement slurry system has low finished product cost and is easy to prepare.

[0008] To achieve the above object, the present invention provides a casing change mitigation cement slurry system. The raw materials of the casing change mitigation cement slurry system include, by weight percentage: 100 parts of G-grade oil well cement, 3-6 parts of microsilicon, 15-50 parts of glass microspheres, 3-6 parts of reinforcing material, 3-5 parts of toughening material, 0-2 parts of stabilizer, 0-2.5 parts of dispersant, 3-6 parts of fluid loss reducer, 0-2.5 parts of retarder, 0.2-0.5 parts of defoamer, 0.2-0.5 parts of antifoaming agent, and 70-95 parts of water;

[0009] The toughening material is compounded by fibers and carbon materials in a mass ratio of 2-4:1, the fibers include one or a combination of two or more of basalt fibers, alumina fibers, and silicon carbide fibers, and the carbon materials include carbon nanotubes and / or expanded graphite;

[0010] The compressive strength of the glass microspheres is 3000-5000 psi.

[0011] In the above-mentioned casing change relief cement slurry system, preferably, the compressive strength of the glass microspheres is 4000psi.

[0012] The present invention reduces the elastic modulus of cement paste without affecting its compressive strength by adding glass microbeads with low compressive strength and toughening materials formed by a compound of fiber and carbon materials. The internal glass microbeads are broken before the cement paste reaches its own compressive resistance limit and is destroyed, thereby providing a certain buffer space for casing deformation and gradually enhancing the cement paste's ability to alleviate casing deformation.

[0013] In the above-mentioned casing change mitigation cement slurry system, preferably, the fiber length of the basalt fiber is 1.5-10 μm.

[0014] In the above-mentioned sleeve change mitigation cement slurry system, preferably, the fiber length of the alumina fiber is 3-6 μm.

[0015] In the above-mentioned casing change mitigation cement slurry system, preferably, the fiber length of the silicon carbide fiber is 10-15 μm.

[0016] In the above-mentioned casing change mitigation cement slurry system, preferably, the length of the carbon nanotubes is 10-30 μm.

[0017] In the above-mentioned casing deformation mitigation cement slurry system, preferably, the particle size of the expanded graphite is 40-50 μm.

[0018] In the above-mentioned casing change mitigation cement slurry system, preferably, the average particle size of the microsilica is 4-10 μm, and the 45 μm sieve residue is ≤5%.

[0019] In the above-mentioned sleeve change mitigation cement slurry system, preferably, the true density of the glass microspheres is 0.38-0.42 g / cm 3 , more preferably 0.40 g / cm 3 The present invention optimizes the true density of the glass microspheres. When the true density of the glass microspheres is too large, the space that can be provided after being broken is limited.

[0020] In the above-mentioned casing change mitigation cement slurry system, preferably, the stabilizer is an ore powder stabilizer and / or a polymer stabilizer, more preferably an ore powder stabilizer.

[0021] In the above-mentioned casing change mitigation cement slurry system, preferably, the dispersant is a condensation product of formaldehyde and acetone and / or a polystyrene sulfonate dispersant.

[0022] In the above-mentioned casing change mitigation cement slurry system, preferably, the fluid loss reducer is a polyacrylamide-based fluid loss reducer.

[0023] In the above-mentioned sleeve change mitigation cement slurry system, preferably, the retarder is an acrylamide retarder.

[0024] In the above-mentioned casing change mitigation cement slurry system, preferably, the defoaming agent includes one or a combination of two or more of tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.

[0025] According to a specific embodiment of the present invention, preferably, the 7-day compressive strength of the cement paste formed by the sleeve-change relief cement slurry system is greater than 20 MPa, and the elastic modulus is less than 5 GPa.

[0026] According to a specific embodiment of the present invention, preferably, the density of the sleeve change mitigation cement slurry system is 1.30-1.60 g / cm 3 , the applicable temperature range is 30-150℃.

[0027] The present invention also provides a method for preparing the above-mentioned sleeve change relief cement slurry system, which comprises: weighing raw materials in proportion and mixing them, and stirring them evenly at a speed of 11500-12500r / min to obtain the sleeve change relief cement slurry system.

[0028] According to a specific embodiment of the present invention, preferably, the method for preparing the sleeve change mitigation cement slurry system comprises the following steps:

[0029] Weigh oil well cement, microsilica, glass microspheres, reinforcing material, toughening material, stabilizer and dispersant in proportion, mix them evenly to obtain a dry mixed material;

[0030] Weigh the fluid loss reducer, retarder and defoamer in proportion and stir them evenly in water to obtain a wet mix solution;

[0031] At a rotation speed of 3800-4200 r / min, the dry mix is ​​evenly poured into the wet mix. After the dry mix is ​​completely added to the wet mix, the stirrer speed is adjusted to 11500-12500 r / min, and stirring is continued to obtain the set change mitigation cement slurry system.

[0032] The present invention also provides an application of the above casing deformation mitigation cement slurry system in shale gas well cementing and preventing and / or mitigating casing deformation.

[0033] The technical solution provided by the present invention has the following beneficial effects:

[0034] The casing change mitigation cement slurry system provided by the present invention meets the requirements of cementing construction. At the same time, the cement stone has a low elastic modulus, and can actively break to exchange space when the formation slip is large, providing space for casing deformation, and has good effects in preventing and mitigating casing change. In some specific embodiments, the 7-day compressive strength of the cement stone formed by the casing change mitigation cement slurry system of the present invention is greater than 20MPa, and the elastic modulus is less than 5GPa. DETAILED DESCRIPTION

[0035] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0036] Description of the raw materials used in the embodiments of the present invention:

[0037] G-grade oil well cement is high sulfate resistance (HSR) G-grade oil well cement, produced by Dalian Cement Group Co., Ltd.;

[0038] The stabilizer is a mature product produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., and its trade name is "DRB-1S, a reinforcing material ore powder for oil well cementing".

[0039] Basalt fibers are commercially available with a fiber length of 1.5-10 μm;

[0040] Alumina fibers are commercially available with a fiber length of 3-6 μm;

[0041] The length of silicon carbide fiber is 10-15 μm;

[0042] Carbon nanotubes, 95% purity, 10-30 μm in length;

[0043] Expanded graphite is commercially available with a purity of more than 95% and a particle size of 48 μm (mesh number 300 mesh);

[0044] Microsilica is commercially available with an average particle size of 5 μm and a 45 μm sieve residue of ≤5%;

[0045] The dispersant is a condensation product of formaldehyde and acetone or a polystyrene sulfonate dispersant;

[0046] Fluid loss reducer is a type of polyacrylamide;

[0047] The defoaming agent is one of tributyl phosphate, polyoxypropylene glycerol and polydimethylsiloxane commonly used in the art.

[0048] Example 1

[0049] This embodiment provides a sleeve change mitigation cement slurry system, and the preparation method thereof is as follows:

[0050] 1. Formula

[0051] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 5 parts of microsilicon, 10 parts of reinforcing material, 4 parts of toughening material, 13 parts of glass microspheres, 1 part of stabilizer, 1.5 parts of dispersant, 3.5 parts of fluid loss reducer, 0.8 parts of retarder, 0.5 parts of defoamer, 0.5 parts of antifoaming agent, and 70 parts of water; wherein the toughening material is formed by uniformly stirring 2 parts of basalt fiber and 1 part of expanded graphite; the true density of the glass microspheres is 0.40 g / cm 3 , compressive strength is 4000psi.

[0052] 2. Preparation method

[0053] Weigh oil well cement, microsilica, glass microspheres, reinforcing materials, toughening materials, stabilizers, and dispersants in proportion and mix them evenly to obtain dry mixed materials. Weigh fluid loss reducer, retarder, and defoamer in proportion and stir them evenly in water to obtain wet mixed medicine. Pour the dry mixed material evenly into the wet mixed medicine at a speed of 4000r / min. After the dry mixed material is completely added to the wet mixed medicine, cover the stirring cup lid, adjust the stirrer speed to 12000r / min, and continue stirring for 35s to obtain the sleeve change relief cement slurry system. After testing, the density of the cement slurry is 1.6g / cm 3 .

[0054] Example 2

[0055] This embodiment provides a sleeve change mitigation cement slurry system, and the preparation method thereof is as follows:

[0056] 1. Formula

[0057] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 5 parts of microsilicon, 10 parts of reinforcing material, 4 parts of toughening material, 32 parts of glass microspheres, 1 part of stabilizer, 1.5 parts of dispersant, 3.5 parts of fluid loss reducer, 0.8 parts of retarder, 0.5 parts of defoamer, 0.5 parts of antifoaming agent, and 75 parts of water; wherein the toughening material is formed by uniformly stirring 3 parts of silicon carbide fiber and 1 part of expanded graphite; the true density of the glass microspheres is 0.40 g / cm 3 , compressive strength is 4000psi.

[0058] 2. The preparation method is the same as in Example 1. The density of the cement slurry is 1.45 g / cm 3 .

[0059] Example 3

[0060] This embodiment provides a sleeve change mitigation cement slurry system, and the preparation method thereof is as follows:

[0061] 1. Formula

[0062] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 5 parts of microsilicon, 10 parts of reinforcing material, 4 parts of toughening material, 50 parts of glass microspheres, 1 part of stabilizer, 1.5 parts of dispersant, 3.5 parts of fluid loss reducer, 0.8 parts of retarder, 0.5 parts of defoamer, 0.5 parts of antifoaming agent, 78 parts of water; wherein the toughening material is formed by uniformly stirring 4 parts of alumina fiber and 1 part of carbon nanotube; the true density of the glass microsphere is 0.40g / cm 3 , compressive strength is 4000psi.

[0063] 2. The preparation method is the same as in Example 1. The cement slurry density is 1.3 g / cm 3 .

[0064] Comparative Example 1

[0065] This comparative example provides a cement slurry system, the formula and preparation method of which are the same as those of Example 1, except that no toughening material is added in this comparative example, and the true density of the glass microspheres used is 0.63 g / cm 3 , the compressive strength is 15000psi; at the same time, in order to keep the density of cement slurry unchanged, the weight proportion of water is changed to 68 parts.

[0066] Comparative Example 2

[0067] This comparative example provides a cement slurry system, the formula and preparation method of which are the same as those of Example 2, except that no toughening material is added in this comparative example, and the true density of the glass microspheres is 0.60 g / cm 3 , the compressive strength is 12000psi; at the same time, in order to keep the density of cement slurry unchanged, the weight proportion of water is changed to 73 parts.

[0068] Comparative Example 3

[0069] This comparative example provides a cement slurry system, the formula and preparation method of which are the same as those of Example 3, except that no toughening material is added in this comparative example, and the true density of the glass microspheres is 0.60 g / cm 3 , the compressive strength is 12000psi; at the same time, in order to keep the density of cement slurry unchanged, the weight proportion of water is changed to 76 parts.

[0070] Experimental example

[0071] The experiment was carried out in accordance with the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement" to evaluate the conventional engineering properties (density, fluidity, API water loss) as well as the compressive strength and elastic modulus of the cement slurry system.

[0072] The main experimental instruments are: 30-60 type tile stirrer; TG7370D type pressurized curing kettle, Shenyang Tiger Petroleum Instrument Equipment Manufacturing Co., Ltd.; HH-420 type constant temperature digital display water tank, Changzhou Yineng Experimental Instrument Factory; YAW-300B hydraulic pressure testing machine, Jinan Xinshijin Testing Machine Co., Ltd.

[0073] This experimental example also uses the following method to test the breakage rate of glass beads under specified conditions:

[0074] 1. Measurement principle

[0075] The crushing rate is determined based on the change in density before and after compression of the sample under a specified pressure.

[0076] 2. Instruments and Equipment

[0077] Strength tester, nitrogen (purity 99.9%), analytical balance.

[0078] 3. Experimental steps

[0079] (1) First, take (2-5) g of sample to measure the true density. The instrument used is 3H-2000TD2 true density measuring instrument produced by Beijing Best Instrument Technology Co., Ltd. (or other instruments with the same true density measurement function);

[0080] (2) Take (2-5)g of the same batch and put them into the sample chamber, put the sample chamber into the high-pressure chamber, and tighten the bolts of the high-pressure chamber;

[0081] (3) Open the nitrogen valve and fill with nitrogen to make the nitrogen pressure reach the required pressure. Keep the pressure constant for 5 minutes, release the pressure, take out the sample and measure the true density. The instrument used is the 3H-2000TD2 true density measuring instrument produced by Best Instrument Technology (Beijing) Co., Ltd. (or other instruments with the same true density measurement function).

[0082] 4. Calculation of crushing rate

[0083] The density of the samples before and after compression is calculated according to the following formula:

[0084] R=ρ0×(ρ2-ρ2) / ρ2 / (ρ0-ρ1)×100

[0085] Where:

[0086] R—crushing rate under specified conditions, %;

[0087] ρ0—True density of the sample when it is completely crushed, g / cm 3 ;

[0088] ρ1—density of the sample before compression, g / cm 3 ;

[0089] ρ2—density of the sample after compression, g / cm 3 .

[0090] The test results of the cement slurry systems of the above embodiments and comparative examples are shown in Table 1.

[0091] Table 1 Cement slurry system performance test results

[0092]

[0093] It can be seen from the data in Table 1 that the fluidity of the cement slurry systems of Examples 1-3 is greater than 20 cm, and the API water loss is less than 50 mL, which meets the requirements of cementing construction; the 7-day compressive strength of the cement stone formed by the cement slurry systems of Examples 1-3 is greater than 20 MPa, and the elastic modulus is less than 5 GPa, with good performance, meeting the cementing sealing requirements.

[0094] It can be seen from the test results of Comparative Examples 1-3 that without adding toughening materials, the compressive strength of the cement stone formed is greater than 20MPa, but the 7-day elastic modulus is relatively high, and the cement stone has poor deformability during stratum sliding, which easily leads to stress concentration; in addition, when the stratum stress reaches the compressive strength limit of the cement stone, the cement stone breaks, and at this time the internal high-compression glass bead structure is basically intact and cannot provide space for the sleeve to deform.

[0095] Comparing the results of comparative example 1 and example 1, it can be seen that the conventional properties of the cement slurry such as API water loss, fluidity, and compressive strength of the two do not change much, and both meet the construction requirements. Compared with comparative example 1, after adding toughening material and replacing glass microspheres with a compressive strength of 4000pasi in example 1, the elastic modulus of the cement stone formed decreased from 7.94GPa to 4.92GPa, and the brittleness of the cement stone decreased significantly. Before the compression resistance of the cement stone reached its own compression resistance limit and was damaged, the internal glass microspheres were broken (the crushing rate was 95.1%), providing a large deformation space, which can provide a certain buffer space for casing deformation.

[0096] Compared with Comparative Example 2, after adding toughening material and replacing glass beads with a compressive strength of 4000pasi in Example 2, the conventional properties of the cement slurry such as API water loss, fluidity, and compressive strength of the two do not change much, and both meet the construction requirements; however, the elastic modulus of Example 2 decreases by 2.95Gpa, and the elastic modulus of the cement stone is significantly reduced. When the stratum slips, the crushing of the glass beads (the crushing rate is 96.6%) can provide a larger deformation space, thereby providing a certain buffer space for the deformation of the casing.

[0097] Compared with Comparative Example 3, after adding toughening material and replacing glass beads with a compressive strength of 4000pasi in Example 3, the conventional properties of the cement slurry such as API water loss, fluidity, and compressive strength of the two do not change much, and both meet the construction requirements; however, the elastic modulus of Example 2 decreases by 2.91Gpa, and the elastic modulus of the cement stone is significantly reduced. When the stratum slips, the crushing of the glass beads (the crushing rate is 95.1%) can provide a larger deformation space, thereby providing a certain buffer space for the deformation of the casing.

[0098] In summary, the present invention provides a sleeve change mitigation cement slurry system with a density of 1.30-1.60 g / cm 3 The applicable temperature range is 30-150℃, the 7-day cement stone compressive strength is greater than 20MPa, and the elastic modulus is less than 5GPa. At the same time, the settlement stability and rheological properties are good, which meets the requirements of cementing construction.

[0099] The above-mentioned embodiments are only embodiments of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person skilled in the art, without departing from the concept of the present invention, several variations, equivalent substitutions, improvements, etc. can be made, which all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.

Claims

1. A cement slurry system for mitigation of changes, wherein the raw materials thereof include, by weight percentage: 100 parts of G-grade oil well cement, 3-6 parts of microsilicon, 15-50 parts of glass microspheres, 3-6 parts of reinforcing material, 3-5 parts of toughening material, 0-2 parts of stabilizer, 0-2.5 parts of dispersant, 3-6 parts of fluid loss reducer, 0-2.5 parts of retarder, 0.2-0.5 parts of defoamer, 0.2-0.5 parts of antifoaming agent, 70-95 parts of water; The toughening material is compounded by fibers and carbon materials in a mass ratio of 2-4:1, the fibers include one or a combination of two or more of basalt fibers, alumina fibers, and silicon carbide fibers, and the carbon materials include carbon nanotubes and / or expanded graphite; The compressive strength of the glass microspheres is 3000-5000 psi.

2. The sleeve change mitigation cement slurry system according to claim 1, wherein: The compressive strength of the glass microspheres is 4000 psi.

3. The sleeve change mitigation cement slurry system according to claim 1, wherein: The fiber length of the basalt fiber is 1.5-10 μm; Preferably, the fiber length of the alumina fiber is 3-6 μm; Preferably, the silicon carbide fiber has a fiber length of 10-15 μm.

4. The sleeve change mitigation cement slurry system according to claim 1, wherein: The length of the carbon nanotubes is 10-30 μm.

5. The sleeve change mitigation cement slurry system according to claim 1, wherein: The particle size of the expanded graphite is 40-50 μm.

6. The sleeve change mitigation cement slurry system according to claim 1, wherein: The true density of the glass microspheres is 0.38-0.42 g / cm 3 , preferably 0.40 g / cm 3 .

7. The sleeve change mitigation cement slurry system according to claim 1, wherein: The average particle size of the micro silicon is 4-10 μm, and the 45 μm sieve residue is ≤5%.

8. The sleeve change mitigation cement slurry system according to claim 2, wherein: The stabilizer is an ore powder stabilizer and / or a polymer stabilizer.

9. The sleeve change mitigation cement slurry system according to claim 2, wherein: The dispersant is a condensation product of formaldehyde and acetone and / or a polystyrene sulfonate dispersant.

10. The sleeve change mitigation cement slurry system according to claim 2, wherein: The fluid loss reducer is a polyacrylamide fluid loss reducer; Preferably, the retarder is an acrylamide retarder; Preferably, the defoaming agent includes one or a combination of two or more of tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.

11. The sleeve change mitigation cement slurry system according to any one of claims 1 to 10, wherein: The 7-day compressive strength of the cement paste formed by the sleeve-change relief cement slurry system is greater than 20 MPa, and the elastic modulus is less than 5 GPa.

12. The sleeve change mitigation cement slurry system according to claim 11, wherein: The density of the sleeve change relief cement slurry system is 1.30-1.60 g / cm 3 , the applicable temperature range is 30-150℃.

13. A method for preparing the sleeve change mitigation cement slurry system according to any one of claims 1 to 12, comprising: The raw materials are weighed in proportion and mixed, and stirred evenly at a speed of 11500-12500 r / min to obtain the sleeve deformation mitigation cement slurry system.

14. The method for preparing the sleeve change mitigation cement slurry system according to claim 13, wherein: The steps include: Weigh oil well cement, microsilica, glass microspheres, reinforcing material, toughening material, stabilizer and dispersant in proportion, mix them evenly to obtain a dry mixed material; Weigh the fluid loss reducer, retarder and defoamer in proportion and stir them evenly in water to obtain a wet mix solution; At a rotation speed of 3800-4200 r / min, the dry mix is ​​evenly poured into the wet mix. After the dry mix is ​​completely added to the wet mix, the stirrer speed is adjusted to 11500-12500 r / min, and stirring is continued to obtain the set change mitigation cement slurry system.

15. Use of the casing deformation mitigation cement slurry system according to any one of claims 1 to 12 in cementing shale gas wells and preventing and / or mitigating casing deformation.

Citation Information

Patent Citations

  • Toughened anti-channeling agent for cement and toughened cement for cementing shale gas horizontal well

    CN104291733A

  • Well cementation cement paste system applicable to large-size staged fracturing of shale gas horizontal well

    CN109761547A

  • High-density anti-channeling tough cement paste system for shale gas well cementation as well as preparation method and application of high-density anti-channeling tough cement paste system

    CN114426415A

  • Expanded flexible well cementing grout and preparation method thereof

    CN104371678A

  • High-temperature-resistant anti-channeling emulsion elastic and tough cement paste and preparation method thereof

    CN110937857A

Cited By

  • High-temperature reinforced and toughened oil well cement admixture and preparation method thereof

    CN121377586A